Design a current mirror using body driven technique - Siti Zawana Abdul Rani (Universiti Malaysia Perlis, 2008)
Current mirror or current source is a one of the key elements in analog circuit design. For high performance analog circuit applications, the accuracy and output impedance are the most important parameters to determine the performance of the current mirror. In this project, a new body-driven current mirror that utilizes an adaptive gate bias to provide accurate operation over a wide range of bias currents is presented. The proposed current mirror can operate with an input and output voltage compliance of VDSAT with no level shifting. By using cascode structure, the proposed circuit can increase the output impedance and also reducing the body effect error. In addition, the cascode configuration also will offer the output current which can prevent from channel length effect and obtain the output. Furthermore, the proposed circuit has much better output compare to other conventional current mirror circuit in the sense that it can achieve the input output mismatch. The design was carried out with properly defined simulation runs on Mentor Graphic environment using TSMC (Taiwan Semiconductor Manufacturing Company) 0.357m CMOS rules of technology and ELDO version 6.5_1.1 simulation with Bsim3v3 version 3.1 at 3.3V supply voltage.